UNDERSTANDING THE IMPACT OF TEMPERATURE ON PILOT PERFORMANCE IN FLIGHT - Dimas Endrawan Putra; Efendi; Wisnu Kuncoro; Ikhwanul Qiram; Daniel Dewantoro Rumani (PT Inovasi Pratama Internasional, 2023)
The cockpit of an airplane is the most important space for pilots to fly, interact and communicate with the necessary information. During flight, airplane pilots face various loads, one example is the comfortable working temperature in the cockpit. The health and performance of pilots is a crucial factor in maintaining aviation safety, considering that pilots are the most vital element in the safety aspect of the aviation industry. Currently, thermal comfort is still a topic that is not fully understood. One of the parameters related to thermal comfort in the cockpit is the room temperature in the cockpit to support the performance, comfort and health of the pilot during flight maneuvers. Based on the data that has been collected, the highest cockpit temperature is achieved at 50oC with an aircraft altitude of 1500 ft and the highest human body temperature is achieved at 37.25oC at a height of 1000 ft where based on this data according to SNI 03-6572-2001 thermal comfort is not achieved or even exceeds the threshold. borderline warm comfortable. Various things can affect thermal comfort, especially the effect of temperature on the cockpit, including cockpit design, air circulation, cockpit/aircraft materials, the effect of engine temperature and also several other factors that have a dominant role in influencing the temperature of the cockpit.